Preliminary Evaluation of Probiotic Properties of Lactobacillus Strains Isolated from Sardinian Dairy Products. (26th June 2014) - Pisano, Maria Barbara; Viale, Silvia; Conti, Stefania; Fadda, Maria Elisabetta; Deplano, Maura; Melis, Maria Paola; Deiana, Monica; Cosentino, Sofia
Abstract : Twenty-three Lactobacillus strains of dairy origin were evaluated for some functional properties relevant to their use as probiotics. A preliminary subtractive screening based on the abilities to inhibit the growth of microbial pathogens and hydrolyze conjugated bile salts was applied, and six strains were selected for further characterization including survival under gastrointestinal environmental conditions, adhesion to gut epithelial tissue, enzymatic activity, and some safety properties. All selected strains maintained elevated cell numbers under conditions simulating passage through the human gastrointestinal tract, well comparable to the values obtained for the probiotic strain Lactobacillus rhamnosus GG, and were able to adhere to Caco-2 cells to various extents (from 3 to 20%). All strains exhibited high aminopeptidase, and absent or very low proteolytic and strong β -galactosidase activities; none was found to be haemolytic or to produce biogenic amines and all were susceptible to tetracycline, chloramphenicol, erythromycin, ampicillin, and amoxicillin/clavulanic acid. Our results indicate that the Lactobacillus strains analyzed could be considered appropriate probiotic candidates, due to resistance to GIT simulated conditions, antimicrobial activity, adhesion to Caco-2 cell-line, and absence of undesirable properties. They could be used as adjunct cultures for contributing to the quality and health related functional properties of dairy products.